PSYCHOLOGICAL PECULIARITIES OF BILINGUALISM (ResearchJet Journal of Analysis and Inventions, 2021)
This article helps articulate some of the multilayered issues that speaking two languages rather than just one has obvious practical benefits in an increasingly globalized world.